FDR and the End of Empire - O'Sullivan, C. author. aut Link
X, 208 p.
Keywords: Based upon extensive archival research in Great Britain, the United States, and the Middle East, including sources never previously utilized such as declassified intelligence records, postwar planning documents, and the personal papers of key officials, this is painstakingly researched account of the origins of American involvement in the Middle East during the Presidency of Franklin D. Roosevelt. It explores the effort to challenge British and French power, and the building of new relationships with Iraq, Iran, Saudi Arabia, Egypt, and the Levant states. It also reveals new and controversial discoveries about Roosevelt's views on Palestine, his relations with Middle East leaders, and his often bitter conflicts with Churchill and de Gaulle over European imperialism. Modern-day parallels make this story compelling for followers of current events, World War II, Franklin Roosevelt, the Middle East, or British imperialism.